Transmetalation reaction between hydrophobic silver nanoparticles and aqueous chloroaurate ions at the air - Water interface - Pasricha, R; Swami, A; Sastry, M (Journal of Physical Chemistry B, 2005)
The transmetalation reaction between a sacrificial nanoparticle and more noble metal ions in solution has emerged as a novel method for creating unique hollow and bimetallic nanostructures. In this report, we investigate the possibility of carrying out the transmetalation reaction between hydrophobic silver nanoparticles assembled and constrained at the air-water interface and subphase gold ions. We observe that facile reduction of the subphase gold ions by the sacrificial silver nanoparticles occurs resulting in the formation of elongated gold nanostructures that appear to cross-link the sacrificial silver particles. This transmetalation reaction may be modulated by the insertion of an electrostatic barrier in the form of an ionizable lipid monolayer between the silver nanoparticles and the aqueous gold ions that impacts the gold nanoparticle assembly. Transmetalation reactions between nanoparticles constrained into a close-packed structure and appropriate metal ions could lead to a new strategy for metallic cross-linking of nanoparticles and generation of coatings with promising optoelectonic behavior.